دراسة وتصميم نظام عزل اهتزازي فعال لحماية الآلات الدوارة ذات الكتل الكبيرة من الاهتزازات - خنيسي, محمد (Latakia University Journal -Engineering Sciences Series, 2019)
يسمح استخدام تكنولوجيا الاهتزازات بتطوير العمليات التكنولوجية التقليدية بشكل جذري، هذا وتؤدي الزيادة الكبيرة لسرعات حركة الآليات والآلات إلى زيادة الاهتزازات واتساع الطيف الاهتزازي مما يتطلب تطوير أنظمة عزل اهتزازي وابتكار حلول بناءة. تستخدم تكنولوجيا الاهتزازات في علم الميتالورجيا (المعادن) وفي عمليات استخراج الثروات الباطنية (النفط والغاز والفحم). تهدف هذه الدراسة إلى إيجاد نظام عزل اهتزازي فعال لحماية الآلات الدوارة ذات الكتل الكبيرة من الاهتزازات وبالتالي فإن إمكانية البحث في ديناميك الآلات الاهتزازية ذات المحاور الدوارة غير المتوازنة يبدو واقعياً جداً. حيث دلت الدراسة على أهمية موازنة الآلات ذات المحاور الدوارة غير المتوازنة يطيل في عمر هذه الآلات ويعطي مردوداً أفضل. Using of vibrations technology enables the development of traditional technological operation. The high increase of movement speed of machines causes an increase in vibrations (vibrational spectrum) which requires the development of vibrational isolation systems and the innovation of thorow solutions. This study aims to build an effective vibrational isolation system to protect rotational big-mass machines, consequently research possibility in dynamic vibrational machines with rotational axis unbalanced seems very realistic. Use vibrational technology in metalorgy and in the extraction of underground resources such as oil, gas and coal. Because balancing of machines with unbalanced rotational axis lengthens the age of these machines and improves the efficiency.